Migration, Orientation and Navigation: Magnetic Compasses in Insects (2010)
The use of magnetic information for orientation and navigation is a widespread phenomenon in animals. In contrast to our knowledge of navigational systems in vertebrates, our understanding of the mechanisms underlying the insect magnetic perception and use of the information is at an early stage. Some insects use magnetic information for simple body alignment or homing. There is also some evidence that insects might use the Earth’s magnetic field to orient during long-distance migrations. In most known cases, insects use a polarity compass, orienting by the North–South axis of the Earth’s magnetic field. However, recent studies have also pointed to a role for magnetic inclination in insect orientation. Also, magnetic information is coupled with other navigation compasses or cues, such as the sun or significant landmarks. The use of traditional insect models will be critical to increasing our knowledge of the proximal mechanisms. Nevertheless, the study of new species is necessary for the solution of specific questions regarding perception, processing, and use of magnetic information in insects. In this article, our current knowledge on the use of magnetic information for orientation and navigation in insects is broadly reviewed, from the nature of the magnetic compass to the diversity of its uses. Important directions for future research are also discussed.